Bioenergy as a Key Driver of Energy Transition: A Case Study of Emission Reduction and Energy Security - Saiful, Rifki; Nur, Syukri M (Universitas Medan Area, 2025)
The transition to renewable energy is an urgent step in addressing the global climate crisis and reducing dependence on fossil fuels, which have increased greenhouse gas emissions and exacerbated climate change. In this context, bioenergy emerges as an important solution because it not only helps reduce carbon emissions through cleaner and carbon-neutral combustion but also increases energy security by diversifying energy sources, especially through the utilization of organic biomass such as agricultural and forestry waste. This study aims to study more deeply about bioenergy as a key driver of energy transition through case studies related to emission reduction and energy security enhancement. Bioenergy plays an important role in the global energy transition because it is able to reduce dependence on fossil fuels and reduce carbon emissions. In addition to helping create a more resilient energy system by utilizing local biomass resources, bioenergy also supports the principle of a circular economy through the utilization of organic waste. Despite offering many benefits, bioenergy development faces challenges such as resource supply and production efficiency, but the opportunities to overcome these challenges remain large through technological innovation and supportive policies. Bioenergy plays an important role in the global energy transition towards clean energy by reducing carbon emissions and increasing energy security through the utilization of renewable biomass. Despite challenges in terms of policy, technology, and raw material supply, the great potential of bioenergy can be optimized through innovation and policy support to strengthen a more sustainable energy system. This study shows that bioenergy has great potential to reduce carbon emissions and increase energy security through the use of renewable biomass, but further development is needed to overcome efficiency and policy challenges to support the transition to a more sustainable energy system.